The World Is Not Enough! Small Open Economies and Regional Dependence - Knut Are Aastveit; Hilde C. Bjørnland; Leif Anders Thorsrud (Norges Bank, 2011)
This paper bridges the new open economy factor augmented VAR (FAVAR) studies with the recent findings in the business cycle synchronization literature emphasizing the importance of regional factors. That is, we estimate and identify a three block FAVAR model with separate world, regional and domestic blocks and study the transmission of both global and regional shocks to four small open economies (Canada, New Zealand, Norway and UK). The results show that foreign shocks explain a major share of the variance in all countries, most so shocks that are common to the world. However, regional shocks also play an important role, explaining more than 20 percent of the variance in the variables. Hence in small open economies, the world is not enough. The regional factors impact the four countries differently, though, some through trade and some through consumer sentiment. Our findings of a strong transmission of both global and regional shocks to open economies are in sharp contrast to the evidence from recently developed open economy DSGE models.
hdl:11250/2496944
Keywords: C32; E32; F41; 330; FAVAR; factor augmented VAR; international transmission; world and region; small open economy; business cycles